RF gun for ILU-12 accelerator - Auslender, V.L.; Gornakov, I.V.; Kuznetsov, G.I.; Makarov, I.G.; Matyash, N.V.; Ostreiko, G.N.; Panfilov, A.D.; Serdobintsev, G.V.; Tarnetsky, V.V.; Tiunov, M.A. (Вопросы атомной науки и техники, 2008)
RF gun for ILU-12 accelerator is described in the paper. Mechanism of beam transportation and energy spectrum
improvements by applying an additional RF voltage of the operating frequency to the cathode-grid gap is considered
in detail. Simulated energy spectrum and density profile of electron beam at the accelerator output are presented. Дається опис ВЧ-гармати прискорювача ІЛУ-12. Детально розглядається механізм поліпшення проходження пучку і його енергетичного спектра шляхом подачі додаткової ВЧ-напруги робочої частоти на зазор сітка-катод. Приводяться розрахункові спектр енергії і профіль щільності електронного пучку на виході прискорювача. Дается описание ВЧ-пушки ускорителя ИЛУ-12. Детально рассматривается механизм улучшения прохождения пучка и его энергетического спектра путем подачи дополнительного ВЧ-напряжения рабочей частоты на зазор сетка-катод. Приводятся расчетные спектр энергии и профиль плотности электронного пучка на выходе ускорителя.